Making Headlines in a State of Emergency: The Case of the Times of Cyprus, 1955–1960. Issue 1 (2nd January 2017) - Stubbs, Jonathan
ABSTRACT: The final years of British rule in Cyprus were marked by the colonial government's use of authoritarian measures to impose control over the local press. The most problematic publication during the 1955–60 period was the Times of Cyprus, an English-language newspaper edited and owned by experienced British journalist Charles Foley. This article examines the fraught relationship between Foley's newspaper and the colonial government against a backdrop of social instability and political violence. In particular, it focuses on the role the newspaper played as a conduit of information between Cyprus and Britain, conveying the experience of colonial rule to influential readers in London and reporting British support for self-determination to a Cypriot reading public. This ability to undermine official control over the flow of intelligence between the colonial periphery and its metropolitan centre unsettled the British administration, leading to repeated but ultimately unsuccessful efforts to proscribe the newspaper.